2021
DOI: 10.1080/23311916.2021.1960250
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smallholder farmers’ participation and level of participation in small-scale irrigation practice in Gemechis district, West Hararghe Zone, Ethiopia

Abstract: The study was conducted to assess factors that determine a household's participation and intensity of use in the Gemechis district. A multi-stage sampling technique was employed and 167 sample households were selected by using the Cochran formula. Both quantitative and qualitative data types from primary and secondary sources were collected. Cross-sectional data were gathered through a semi-structured questionnaire survey. For both dummy and continuous variables, chi-square (χ2) and independent t-test statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(13 reference statements)
1
6
1
Order By: Relevance
“…As a result, at a level of significance of less than 5%, the gender of farm households and the decision about irrigation use were positively connected. e results are similar to those of the results of the binary logit model of Yenealem (2013) and Tale et al [63]. ey suggest that gender influences the adoption of improved maize varieties, and adoption of improved agricultural technology is less intense in female-headed households where decisions are made jointly by men and women than in male-headed households where decisions are made jointly (Table 10).…”
Section: Sex Of Household Headsupporting
confidence: 85%
See 1 more Smart Citation
“…As a result, at a level of significance of less than 5%, the gender of farm households and the decision about irrigation use were positively connected. e results are similar to those of the results of the binary logit model of Yenealem (2013) and Tale et al [63]. ey suggest that gender influences the adoption of improved maize varieties, and adoption of improved agricultural technology is less intense in female-headed households where decisions are made jointly by men and women than in male-headed households where decisions are made jointly (Table 10).…”
Section: Sex Of Household Headsupporting
confidence: 85%
“…As a result, the decision on age and irrigation use was positively associated at a significance level of less than 5%. e findings contradict those of Yenealem (2013) and Tale 10 Advances in Agriculture et al [63], who discovered that age and small-scale irrigation have no relationship.…”
Section: E Age Of Farm Householdcontrasting
confidence: 64%
“…Although considerable efforts were exerted by research and development practitioners to introduce improved technologies, most famers in Ethiopia grow sesame traditionally. Farmers use local sesame cultivars and majority of them do not apply fertilizer (Gedefa, 2010;H. G. Hailu & Mezegebo, 2021;Teklu et al, 2021;Yalew et al, 2020).…”
Section: Evidence That This Is a Problemmentioning
confidence: 99%
“…The low productivity of sesame is mainly due to low adoption of recommended technologies in sesame growing areas (Dabessa et al, 2019;Gebremedhn et al, 2019;Gedefa, 2010;Teklu et al, 2021;Weyessa, 2017;Yalew et al, 2020). A meta-analysis by Feyisa (2020) showed that age of the household head, education level, farm size, livestock holding, access to extension services, access to credit services, cooperative membership, and distance from the market are the main determinants of technology adoption in Ethiopia.…”
Section: Prevalence Of the Problemmentioning
confidence: 99%
“…Studies such as Hassan and Salim, (2011), Ouédraogo et al (2020), and Ayeni (2020), among others, have studied the determinants of private investment, but the results are inconsistent. Many studies have proposed the factors that determine private investment, such as public sector investment (Ribeiro & Teixeira, 2001), (Ayeni, 2020), external debt (Bello Ajide & Lawanson, 2012), interest rates (Akçay & Karasoy, 2020), inflation (Geddafa, 2023), economic growth (Karagöz, 2010), trade openness (Boachie et al, 2020). Despite the importance of private investment in the economic growth process, the results of the studies investigating the determinants of private investment have been mostly varied and inconclusive at best -leaving the importance of this paper undeniable.…”
Section: Introductionmentioning
confidence: 96%